The study on personality and self-efficacy as predictors of adaptive performance among employees at Tenaga Nasional Berhad (TNB) Batu Pahat / Nur Shaheera Jamzuri - Jamzuri, Nur Shaheera (Faculty of Business and Management, 2018)
The purpose of this research is to study on the personality namely conscientiousness, openness to experience and neuroticism and self-efficacy as predictors of adaptive performance among employees at Tenaga Nasional Berhad (TNB) Batu Pahat. Data collected focused on employee at Tenaga Nasional Berhad (TNB) Batu Pahat., Johor which is the utility electricity company in Malaysia. The researcher distributed 80 questionnaires among employees. 105 were returned resulting in a response rate of 76.2%. The analysis of the data revealed that self-efficacy has positive impact on adaptive performance while conscientiousness, openness to experience and neuroticism do not have impact on adaptive performance. The results shows that there is a relationship between self-efficacy and adaptive performance. In conclusion, this research has shown further research opportunities that can enhance the understanding of the variables towards employees’ adaptive performance in the organization.